The Influence of Board of Commissioners, Board of Directors, Board of Commissioners Independent Audit Committee and Board of Trustees to Financial Performance Islamic Banking (Case Study on Islamic Bank Period in 2011-2013) - Riyadi, Slamet; Santoso, Cahyo Budi (Archives of Business Research, 2018)
In practice, BAZNAS or LAZNAS also manages the funds in the form of baitu qiradh (productive economic empowerment), lend funds to productive effort. Thus governance applied by the Organization Manager Zakat have characterized the governance of non-profit organization. The data presented in this section of the research about the management of Zakat based on existing regulations. This indicates that management of zakat more advanced and evolved over the development of other Islamic instruments. The purpose of this study is to The Influence of Board of Commissioners, Board of Directors, the Board of Commissioners Independent, the Audit Committee and the Board of Trustees to the Financial Performance Islamic Banking. The independent variable in this study is Board of Commissioners, Board of Directors, the Board of Commissioners Independent, the Audit Committee and the Board of Trustees, while the dependent variable is the Financial Performance (Y). The sample in this study is eight Islamic Banking (period in 2011-2013). Method of data processing is using multiple linear regression with SPSS. The result of Discussion can be concluded that:The results showed that the perspectives or paradigms about the importance of remuneration or the material world to increase commitment and performance are not as expected by the Maspion Company and employee commitment decreased significantly which may be caused by The Board of Commissioners do not affect financial performance significantly to Islamic banking. The Board of directors do not affect financial performance significantly to Islamic banking. Independent Commissioners have no effect significantly to financial performance of Islamic banking. Audit Committee financial performance significantly to the influential Islamic banking. The Board of Trustees has no effect significantly to financial performance of Islamic banking